Deep Heat: A Comparison of Water Temperature, Anemone Bleaching, Anemonefish Density and Reproduction between Shallow and Mesophotic Reefs - Anne Haguenauer; Frédéric Zuberer; Gilles Siu; Daphne Cortese; Ricardo Beldade; Suzanne C. Mills (Fishes, 2021)
French Polynesia is experiencing increasing coral bleaching events in shallow waters triggered by thermal anomalies and marine heatwaves linked to climate change, a trend that is replicated worldwide. As sea surface thermal anomalies are assumed to lessen with depth, mesophotic deep reefs have been hypothesized to act as refuges from anthropogenic and natural disturbances, the ‘deep reef refugia hypothesis’ (DRRH). However, evidence supporting the DRRH is either inconclusive or conflicting. We address this by investigating four assumptions of the DRRH focusing on the symbiotic association between anemones and anemonefish. First, we compare long-term temperature conditions between shallow (8 m) and mesophotic sites (50 m) on the island of Moorea from 2011–2020. Second, we compare the densities of the orange-fin anemonefish, Amphiprion chrysopterus between shallow and mesophotic (down to 60 m) reefs across three archipelagos in French Polynesia. Finally, we compare the percentage of anemone bleaching, as well as anemonefish reproduction, between shallow and mesophotic reefs. We found that the water column was well mixed in the cooler austral winter months with only a 0.19 °C difference in temperature between depths, but in the warmer summer months mixing was reduced resulting in a 0.71–1.03 °C temperature difference. However, during thermal anomalies, despite a time lag in warm surface waters reaching mesophotic reefs, there was ultimately a 1.0 °C increase in water temperature at both 8 and 50 m, pushing temperatures over bleaching thresholds at both depths. As such, anemone bleaching was observed in mesophotic reefs during these thermal anomalies, but was buffered compared to the percentage of bleaching in shallower waters, which was nearly five times greater. Our large-scale sampling across French Polynesia found orange-fin anemonefish, A. chrysopterus, in mesophotic zones in two high islands and one atoll across two archipelagos, extending its bathymetric limit to 60 m; however, orange-fin anemonefish densities were either similar to, or 25–92 times lower than in shallower zones. Three spawning events were observed at 50 m, which occurred at a similar frequency to spawning on shallower reefs at the same date. Our findings of thermal anomalies and bleaching in mesophotic reefs, coupled with mainly lower densities of anemonefish in mesophotic populations, suggest that mesophotic reefs show only a limited ability to provide refugia from anthropogenic and natural disturbances.